Information and Profits: The Case of Technology Transfer in the Malaysian Electronics Industry - Shankaran Nambiar (Asian Academy of Management Journal, 1997)
Information and Profits: The Case of Technology Transfer in the Malaysian Electronics Industry (PDF not available)